2022
DOI: 10.1021/acsomega.2c00069
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneously Improving the Optical, Dielectric, and Solubility Properties of Fluorene-Based Polyimide with Silyl Ether Side Groups

Abstract: Three fluorene-based polyimides with silyl ether groups (Si–PIs) were successfully synthesized by a simple and efficient silicon etherification reaction of hydroxyl-containing polyimides (OH–PIs) and tert -butylchlorodiphenylsilane (TBDPSCl), and their structures were confirmed by 1 H NMR and IR spectra. The bulky nonpolar tert -butyldiphenylsilyl (TBDPS) side groups in the modified PI unit instead of the strong electron donor −OH group is co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 40 publications
1
1
0
Order By: Relevance
“…8) [75], which also led to enhanced thermal properties (Tg > 311 °C; Td 5% > 469 °C). The same group also reported similar results using tert-butyldiphenylsilylchloride (Figure 8) [76]. 8) [75], which also led to enhanced thermal properties (T g > 311 • C; T d 5% > 469 • C).…”
Section: Examples Of Structural Designs Of Transparent Pi Films With ...supporting
confidence: 52%
See 2 more Smart Citations
“…8) [75], which also led to enhanced thermal properties (Tg > 311 °C; Td 5% > 469 °C). The same group also reported similar results using tert-butyldiphenylsilylchloride (Figure 8) [76]. 8) [75], which also led to enhanced thermal properties (T g > 311 • C; T d 5% > 469 • C).…”
Section: Examples Of Structural Designs Of Transparent Pi Films With ...supporting
confidence: 52%
“…To further reduce the D k (up to 2.44) value, Wu et al modified the fluorene moieties of ODPA-and FDA-based polyimides by directly silylating the pendant hydroxy groups of 9,9-bis(4-aminophenyl)-2,7-dihydroxy-fluorene (Fn1) and 9,9-bis(3-methyl-4-aminophenyl)-2,7-dihydroxy-fluorene (Fn2) with tert-butyldimethylsilylchloride (Figure8)[75], which also led to enhanced thermal properties (T g > 311 • C; T d 5% > 469 • C). The same group also reported similar results using tert-butyldiphenylsilylchloride (Figure8)[76].…”
supporting
confidence: 57%
See 1 more Smart Citation
“…In addition, Zuo and co-workers [28] developed a new strategy to construct low-dielectric-constant PI films by the introduction of meta-substituted and trifluoromethyl structures into the main chains of PI films, in which the meta-substituted structure and trifluoromethyl units could inhibit the transfer of charge transfer complex effects and increase the free volume of PI films, thereby resulting in a lower dielectric constant. Recently, Wu et al [29] reported three fluorene-based PI films with silyl ether structures that delivered a low dielectric constant and high hydrophobicity. The reason is that the bulky nonpolar tert-butyldiphenylsilyl side groups in the PI films are able to decrease the charge transfer interaction and electronic conjugation along the PI chain, and increase the free volume and hydrophobicity of Si-PI films.…”
Section: Introductionmentioning
confidence: 99%
“…In the current work, such PI films were endeavored to be developed based on the fluorene-containing dianhydride, 9,9-bis(3,4dicarboxyphenyl)fluorene dianhydride (FDAn) and the amide-containing diamines. Fluorene groups represent a class of rigid and fused-ring structure with high thermal resistance and bulky molecular volumes [37]. As for the optical and dielectric features, the fluorene groups can usually endow the derived polymer films with good optical transparency, high refractive indices, low birefringence, low optical retardation, and low dielectric constants [38][39][40].…”
Section: Introductionmentioning
confidence: 99%